A new perspective for the treatment of Alzheimer’s Disease: exosome-like liposomes to deliver natural compounds and RNA therapies - Ribeiro, Joana (2023)
With the increment of the aging population in recent years, neurodegenerative diseases exert a major global disease burden, essentially as a result of the lack of treatments that stop the disease progression. Alzheimer’s Disease (AD) is an example of a neurodegenerative disease that affects millions of people globally, with no effective treatment. Natural compounds have emerged as a viable therapy to fill a huge gap in AD management, and in recent years, mostly fueled by the COVID-19 pandemic, RNA-based therapeutics have become a hot topic in the treatment of several diseases. Treatments of AD face significant limitations due to the complex and interconnected pathways that lead to their hallmarks and also due to the necessity to cross the blood–brain barrier. Nanotechnology has contributed to surpassing this bottleneck in the treatment of AD by promoting safe and enhanced drug delivery to the brain. In particular, exosome-like nanoparticles, a hybrid delivery system combining exosomes and liposomes’ advantageous features, are demonstrating great potential in the treatment of central nervous system diseases.